Morphological and quantitative changes in mitochondria, plastids, and peroxisomes during the log-to-stationary transition of the growth phase in cultured tobacco BY-2 cells. (3rd March 2016) - Toyooka, Kiminori; Sato, Mayuko; Wakazaki, Mayumi; Matsuoka, Ken
ABSTRACT: We developed a wide-range and high-resolution transmission electron microscope acquisition system and obtained giga-pixel images of tobacco BY-2 cells during the log and stationary phases of cell growth. We demonstrated that the distribution and ultrastructure of compartments involved in membrane traffic (i.e., Golgi apparatus, multivesicular body, and vesicle cluster) change during the log-to-stationary transition. Mitochondria, peroxisomes, and plastids were also enumerated. Electron densities of mitochondria and peroxisomes were altered during the growth-phase shift, while their numbers were reduced by nearly half. Plastid structure dramatically changed from atypical to spherical with starch granules. Nearly the same number of plastids was observed in both log and stationary phases. These results indicate that mechanisms regulating organelle populations differ from organelle to organelle.